Teachers’ Role in Facilitating Outdoor Game Education: A Qualitative Study in Jingmen Vocational College Pre-school Education Settings - Gong, Zihan (Pacific International Journal, 2024)
Early childhood education serves as a crucial foundation for lifelong learning and development, highlighting the increasing importance of outdoor game education in nurturing physical, cognitive, social, and emotional growth in children. This qualitative study delves into the integral role of teachers within the pre-school education settings at Jingmen Vocational College, examining their perceptions, strategies, challenges, and the impact of outdoor game education on children’s learning outcomes. Teachers in these settings perceive their role as essential in promoting holistic child development and employ various strategies while encountering challenges related to limited resources, weather constraints, and managing diverse needs. Positive outcomes include enhanced physical fitness, problem-solving abilities, creativity, social skills, and emotional well-being in children, along with improvements in independence, self-regulation, communication, and collaboration skills. Implications for practice call for professional development opportunities and resources for teachers, while policy recommendations emphasize the integration of outdoor game education into the curriculum and the allocation of dedicated time, resources, and safety guidelines for outdoor play. Future research should explore long-term effects, strategies to overcome challenges, and conduct comparative studies in various educational contexts, underscoring the pivotal role of teachers in fostering well-structured outdoor game experiences for enhancing children’s overall development and well-being.